1994
DOI: 10.1182/blood.v83.9.2423.2423
|View full text |Cite
|
Sign up to set email alerts
|

LAZ3 rearrangements in non-Hodgkin's lymphoma: correlation with histology, immunophenotype, karyotype, and clinical outcome in 217 patients

Abstract: We have recently shown that an evolutionary conserved gene LAZ3, encoding a zinc finger protein, is disrupted and overexpressed in some B-cell lymphomas (mainly with a large cell component) that show chromosomal rearrangements involving 3q27. Because the breakpoints involved in these rearrangements are focused in a narrow major translocation cluster (MTC) on chromosome 3, we used genomic probes from this region to study the molecular rearrangements of LAZ3 in a large series of patients (217) with non-Hodgkin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(38 citation statements)
references
References 17 publications
2
34
2
Order By: Relevance
“…For the group of patients with low‐grade FL, a gene rearrangement incidence of 6.7% was found. This rate is generally lower compared with Western populations, it is but similar to the findings from Lo Coco et al8 and Bastard et al,25 who demonstrated BCL ‐6 rearrangement in 6–15% of FLs. Furthermore, we also found no transformation of follicular lymphoma in patients with BCL ‐6 gene rearrangement.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For the group of patients with low‐grade FL, a gene rearrangement incidence of 6.7% was found. This rate is generally lower compared with Western populations, it is but similar to the findings from Lo Coco et al8 and Bastard et al,25 who demonstrated BCL ‐6 rearrangement in 6–15% of FLs. Furthermore, we also found no transformation of follicular lymphoma in patients with BCL ‐6 gene rearrangement.…”
Section: Discussionsupporting
confidence: 88%
“…This finding suggests that BCL ‐6 alterations are manifested only in B‐cell NHLs. We identified BCL ‐6 gene rearrangements in samples from 16.9% of patients with DLBCL, an incidence below the 37% and 45% rates reported by Bastard et al25 and Lo Coco et al,8 respectively. The reason for this lower incidence may be due to geographic differences in the pathogenesis of lymphoma or to institutional selection bias.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Identification of each type of DLBCL not only with the IPI but also with biological prognostic factors that directly show the characteristics of the tumor is essential for the establishment of better standard chemotherapy methods for each type. The biological prognostic factors proposed so far are gene abnormality ( TP53 , BCL6 ), serum protein (nm23H1), surface markers, and gene expression profiles (Bastard et al, 1994; Offit et al, 1994; Ichikawa et al, 1997; Jaffe et al, 2001; Niitsu et al, 2001; Rosenwald et al, 2002; Shipp et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A translocation between the immunoglobin heavy chain region on chromosome 14 and the bcl ‐2 gene on chromosome 18 resulting in overexpression of Bcl‐2 protein is implicated in the pathogenesis of over 85% of follicular lymphomas in adults;17, 18 bcl ‐2 involvement in pediatric follicular lymphomas has not been shown. An oncogenic role for p53 and bcl ‐6 has also been proposed for adult follicular lymphoma,19–23 but analysis of pediatric follicular lymphomas is lacking.…”
mentioning
confidence: 99%